HUBUNGAN KETERAMPILAN MEMBATIK DAN MOTORIK HALUS DENGAN KEMAMPUAN MENULIS - DAMAYANTI, ANITA (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
The purpose of this study discover the relationship between handâs fine motoric skill coordination in batik towards writing skill. The study has been finally conducted at the primary school Tunas Muda Ikatan Kesejahteraan Keluarga TNI Pragati Wira Anggini Palmerah, Jakarta Barat. Series of tests as an instruments measured of complete datas on batikâing capability, fine motoric skill coordination as well as writing skill capability. Above findings in Correlation Coefficient at the Batik ability and handâs fine motoric skill coordinationâs Variables; summarized that if given stimulation as well as an extra ordinary induced exercise would automatically contribute the related writing skill capability of 6 - 8 years old primary school students.Keywords: motoric, skill, writing, batik